PERANAN ANALISIS LAPORAN KEUANGAN DALAM MENGEVALUASI KINERJA KEUANGAN PERUSAHAAN PADA PT. BANK JABAR BANTEN Tahun 2007 – 2009 - Anwar, Yuli (Jurnal Ilmiah Binaniaga, 2012)
The purpose of this study was to determine the financial performance of PT Bank Jabar Banten in 2007 - 2009 using a comparison and analysis of financial ratio analysis. The results obtained, the conditions seen from the company 's liquidity position : the current ratio in 2009 decreased because although the amount of current assets increased during the year, but the amount of current liabilities for the year also increased, indicating that the measurement is easy and fast to join the new amount of cash and other current assets by current liabilities. This means that when the securities are sold and accounts receivable payments can be received, then the bank can repay its short-term liabilities. Conditions views of the company 's solvency position, although there is a decrease and an increase in the solvency ratio, but the changes are not so significant or can be said to be relatively stable. This could indicate that the company 's financial performance is good enough to settle its debts - debts. Condition when viewed from the position of company activity , fixed asset turnover and working capital turnover continues to increase each year due to an increase in the side that tends to balance income and fixed assets. Keywords : financial performance, liquidity position, solvency, activity position.